Exploration of various solid forms of novel (1H-Benzimidazole, 2-[4-(1,1-dimethylethyl) phenyl]) - Smruti Rekha Rout; Gowtham Kenguva; Lopamudra Giri; Rambabu Dandela (Results in Chemistry, 2023)
Polymorphism/solid forms are acknowledged to have important implications in the pharmaceutical industry, hence regulating polymorph/solid forms formation is essential. 1H-Benzimidazole, 2-[4-(1,1-dimethylethyl)phenyl] (BDP) drug has been discovered as a transcriptional activator of peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) in certain metabolic tissues. Up to date, there is no solid forms of BDP have been reported. The purpose of this study was to see how changing solvent conditions and co-formers influenced the formation of distinct solid forms of BDP. The solvents were chosen based on their polarity, as different polarity solvents are anticipated to interact differently with APIs, impacting the creation of diverse solid forms. Similarly, two GRAS (Generally Recognized As Safe) co-formers, Oxalic Acid (OA) and Malonic Acid (MA), were employed to test the potential of various forms of BDP to form diverse supramolecular networks that might improve BDP's physicochemical qualities. The experimental finding reveals that one polymorph, two solvates and three molecular salts have been obtained by solvent evaporation (SE) and liquid assisted grinding (LAG) methods. Interestingly, BDP creates a similar channel structure in all the two solvates (acetone and isopropanol). Furthermore, different forms of BDP using the same co-former show different molecular assemblages, confirming the occurrence of multiple forms. PXRD, SCXRD, and thermal analyses were used to characterize all of the synthesized forms. The findings of this study indicate that solvent choice and synthesis process are important factors in polymorph screening and can influence the creation of diverse molecular forms.